KEMAMPUAN KOMUNIKASI MATEMATIS SISWA PADA MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) DAN KOOPERATIF TIPE JIGSAW PADA SISWA SMP - Yayan, Yayan; Zachriwan, Zachriwan (Jurnal Math-UMB.EDU, 2019)
The purpose of the study was found out the differences in students' mathematical communication skills learning model based on problem learning, the cooperative Jigsaw type and conventional learning model. The learned model which the results was better differences in students' mathematical communication between learning models problem based learning (PBL), the learned models cooperative jigsaw type, and the models conventional junior high school students. This type of the research was quasi experiment. This research was conducted at SMP N 10 of Bengkulu at VIII grade 1stÂ  in the academic year 2017/2018. The population of this study was all students of the class VIII consisting of 5 classes. The sample of the research was chosen at randomly that VIII A was given a learning model cooperative jigsaw type, and class VIII D was given a conventional learning model. Mathematical ability of the students gathered with mathematical communication ability test, This test consists of pre-test and post-test. The data was analyzed with one-way ANOVA, followed by BNT test. The results showed that there were differences between students' mathematical communication skills in PBL models,jigsaw models and conventional models. The test was results further suggested was not the difference in the ability of the differences between PBL with Jigsaw. While conventional and jigsaw, PBL with conventional differences.based on the average score of the three models of mathematical communication skills learning, PBL learning model provides results of mathematical communication skills was better.Â Keywords: communication ability, problem based learning, jigsaw